2017
DOI: 10.1016/j.jmgm.2017.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Study of the mechanism of protonated histidine-induced conformational changes in the Zika virus dimeric envelope protein using accelerated molecular dynamic simulations

Abstract: The Zika virus has drawn worldwide attention because of the epidemic diseases it causes. It is a flavivirus that has an icosahedral protein shell constituted by an envelope glycoprotein (E-protein) and membrane protein (M-protein) in the mature virion. The multistep process of membrane fusion to infect the host cell is pH-induced. To understand the mechanism of the conformational changes in the (E-M) protein homodimer embedded in the membrane, two 200-ns accelerated dynamic simulations were performed under dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 74 publications
(89 reference statements)
0
10
0
Order By: Relevance
“…The multistep process of membrane fusion that enables ZIKV to infect target cells is pH-induced [ 52 ]. Sun et al [ 59 ] have demonstrated that conserved residues expressed in E protein were protonated under low pH conditions and played key roles in driving the fusion process. While low pH in endosomal compartments enables ZIKV fusion by inducing conformational changes on ZIKV E protein our results suggest that extracellular acidosis enhances the binding of the viral particles to the cell surface thus increasing viral infectivity.…”
Section: Discussionmentioning
confidence: 99%
“…The multistep process of membrane fusion that enables ZIKV to infect target cells is pH-induced [ 52 ]. Sun et al [ 59 ] have demonstrated that conserved residues expressed in E protein were protonated under low pH conditions and played key roles in driving the fusion process. While low pH in endosomal compartments enables ZIKV fusion by inducing conformational changes on ZIKV E protein our results suggest that extracellular acidosis enhances the binding of the viral particles to the cell surface thus increasing viral infectivity.…”
Section: Discussionmentioning
confidence: 99%
“…MR766 and MR/PR(prM) showed similar pH stability, with indistinguishable pH versus infectivity profiles (Fig 3E). The 3 amino acid changes in M would thus appear not to influence E-M interactions [83] sufficiently to affect pH stability. In addition, pH stability would not appear to be a determining factor in the reduced virulence of MR/PR(prM) when compared with MR766.…”
Section: Role Of Prm Cleavage or Ph Stability In Virulencementioning
confidence: 99%
“…Numerous all-atom and CG simulations of the flavivirus envelope have been reported. For example, several all-atom simulation studies investigated viral envelope conformational changes occurring upon exposure to low pH, both during the fusion and maturation processes [26][27][28][29][30][31][32][33][34]. The capacity for individual E/M proteins or their complexes to initiate membrane fusion [35][36][37][38][39][40] and host membrane bending [41] has also been extensively studied via simulation.…”
Section: Simulations Of Flavivirus Systemsmentioning
confidence: 99%